Prevalence, characteristics and management of chronic cough in people with interstitial lung disease: an exploratory study - Ferreira, Flávia Cardoso (2023)
Background: Chronic cough (CC) is a debilitating symptom, with prevalences between 53% and 84% in people with interstitial lung diseases (ILD) worldwide. However, information on its assessment and management in clinical practice is scarce. In Portugal, the prevalence and characteristics of CC in people with ILD are also unknown. Objective: This study aimed to contribute to establishing the prevalence of CC in people with ILD in Portugal. Secondary aims were to characterize the profile of CC in people with ILD, and the assessment and management strategies of CC in this population. Methods: An observational cross-sectional study was carried with people with ILD and with healthcare professionals who provided direct care to this population in Portugal. Data collection was carried out by completing two online questionnaires. The questionnaire aimed at healthcare professionals had 37 items, and the questionnaire aimed at people with ILD had 62 items. The prevalence of CC in individuals with ILD was calculated using the number of individuals with ILD who answered "yes" to the question "Currently coughing for at least 8 weeks (2 months)" as the numerator, and the total number of participants with ILD as the denominator. Calculation of the prevalence of CC in subgroups was calculated using the same methodology. Results: In total, 69 responses from healthcare professionals and 52 responses from people with ILD were included. The prevalence of CC in people with ILD was 44%. CC was characterized by the presence of a dry cough, present on average for 2 years, being smoke the commonest trigger. The main symptoms associated with CC reported by healthcare professionals were fatigue and dyspnea while for people with ILD was sputum, wheezing and husky voice. The main impact of CC reported by both groups was a decrease in quality of life. CC was reported to be regularly assessed by healthcare professionals, using clinical history, lung function and physical examination. For productive CC healthcare professionals tend to recommend bronchial hygiene techniques and education for managing dry CC. In contrast, individuals with ILD commonly reported pharmacological treatment as the most frequent approach. The majority (81%) of individuals with ILD and CC undergo any treatment and healthcare professionals reported that 15% of people with ILD had refractory CC. Conclusion: About 44% of people with ILD present with CC. Healthcare professionals and people with ILD agree on most of the characteristics related to CC. Although there are discrepancies in opinion regarding the symptoms associated with CC both groups refer to CC as an important symptom that should be regularly evaluated by healthcare professionals. Understanding of these finding can inform health professionals on how to adapt communication, assessment and clinical practice with this population in the future. Future research is needed on the prevalence and characteristics and management of CC in different subtypes of ILD to better understand and treat CC in ILD more efficiently.